The Implementation of Green Accounting Based on University Social Responsibility (USR) in Muhammadiyah University of Sidoarjo - Santi Rahma Dewi; Eny Maryanti (Journal of Economics, Business, and Government Challenges, 2018)
This study aims to determine the application of green accounting based onuniversity social responsibility (USR) at Muhammadiyah University of Sidoarjo.The population in this study were officials at Muhammadiyah University of Sidoarjo. Data collection techniques in this study are documentation and questionnaires. The sampling technique used is simple random sampling. The design of this research is descriptive research. In the questionnaire presents elements of the statement about 1) environmental awareness on the implementation of green accounting based on university social responsibility in UMSIDA. 2) environmental involvement on green accounting implementation based on university social responsibility in UMSIDA 3) environmental report on green accounting implementation based on university social responsibility in UMSIDA 4) environmental audit on green accounting implementation based on university social responsibility in UMSIDA. The result of the research by collecting questionnaires and processing it with SPSS 18.0 got the conclusion that the environmental awareness is high enough indicated by the percentage. Medium environmental involvement because UMSIDA has not implemented green accounting in the policy. With no policy so that the results of the questionnaire for the report is low and environmental audits also do not exist. It is expected that UMSIDA can apply Green Accounting to increase efficiency and operational effectiveness.